The Impact of Vitamin D Supplementation on Asthma Control in Children - Tabassum Bashir, Zoha Rafaqat, Naveed Lodhi, Urooj Yahya, Hussain Ali, Arva Zahid (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Asthma is a common chronic respiratory condition affecting millions of children worldwide. Despite advancements in asthma management, many pediatric patients continue to experience suboptimal control, leading to frequent exacerbations, reduced quality of life, and increased healthcare utilization. Objectives: The main objective of the study is to find the impact of vitamin D supplementation on asthma control in children. Material and methods: A total of 175 pediatric patients aged 6 to 14 years were recruited from the pediatric respiratory clinic at Nawaz Sharif Medical College, Gujrat. Eligible participants were diagnosed with persistent asthma according to the Global Initiative for Asthma (GINA) guidelines. Patients with significant comorbidities, those on vitamin D supplementation, or with a history of vitamin D toxicity were excluded from the study. Results: The study enrolled a total of 175 pediatric patients, with 87 participants in the intervention group and 88 in the control group. The mean age of the participants was 10 years, with a gender distribution of 55% male and 45% female. Baseline characteristics, including age, gender, and asthma severity, were comparable between the two groups. At baseline, the mean ACT score in the intervention group was 14.9, while in the control group, it was 14.7. The mean cACT score was 16.8 in the intervention group and 17.1 in the control group. Practical Implication: This study will be helpful in finding the vitamin D supplementation on asthma control in children. Conclusion: It is concluded that the impact of vitamin D supplementation on asthma control in children provides encouraging evidence for the potential benefits of vitamin D as an adjunctive therapy in pediatric asthma management. The 12-week intervention with daily vitamin D3 supplementation at a dosage of 1000 IU demonstrated significant improvements in asthma control scores and lung function parameters (FEV1 and FVC) in the intervention group compared to the control group. Keywords: Vit-D, Asthma, Patients, Functions